THE CRITERIA DEVELOPMENT FOR THE MANAGEMENT OF INVESTMENT AND CONSTRUCTION PROJECTS, TAKING INTO ACCOUNT UNCERTAINTIES - Herasymova, O. L. (Science and Transport Progress, 2009)
A complex criterion of estimation of efficiency of the management system by the construction projects is developed in the article. It assumes the choice of administrative decisions on the basis of data of project realization statistics and a middle risk of the system.